Comparative Evaluation of Two Different Doses of Dexmedetomidine for Intra Operative Moderate Sedation During Spinal Anesthesia - Ritesh Patel; Gunjan Vadhadiya; Hina Gadani; Shobhana Gupta (Archives of Anesthesia and Critical Care, 2023)
Background: Intravenous (IV) sedation is often used to relieve anxiety or stress during surgery under regional anesthesia. Subarachnoid block is a widely followed regional anaesthesia technique, especially in lower abdominal and lower limb surgeries. Intense sensory and motor block, continuous supine position and the inability to move the body also brings a feeling of discomfort and phobia in many patients. Sedation has been shown to increase patient satisfaction during regional anaesthesia. Dexmedetomidine is well suited for conscious sedation as patient can be quickly aroused and oriented on demand. Aim of this study was to compare infusion doses of 0.3μg/kg/hr and 0.5μg/kg/hr, after loading dose of 1μg/kg of injection (inj).dexmedetomidine in order to obtain a better regimen for patients undergoing procedures under spinal anaesthesia in terms of sedation and hemodynamic stability. Objective: To compare efficacy of dexmedetomidine for intraoperative sedation and hemodynamic stability at doses of 0.3μg/kg/hr and 0.5μg/kg/hr after loading dose of 1 μg/kg in patients operated under spinal anaesthesia. Methods: Adult 80 Patients were randomly divided into two groups, (Group D-0.3) and (Group D-0.5). They were given spinal anaesthesia with 0.5% hyperbaric bupivacaine and initial dose of inj.dexmedetomidine 1 μg/kg was infused over 10 minutes. Group D-0.3 received maintenance dose of inj.dexmedetomidine of 0.3μg/kg/hr and Group D-0.5 received maintenance dose of 0.5μg/kg/hr.  Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), respiratory rate (RR), spO2 and sedation using observer’s assessment of alertness/sedation (OASS) were recorded at baseline, after loading dose, before spinal anesthesia, after spinal anesthesia at every 5 minutes upto 30 minutes, followed by every 15 minutes till the end of surgery and every 5 minutes upto 15 minutes after surgery. Data were compared using chi-square and unpaired t test. Results: The mean age for Group D-0.3 is 43.9+11 and for Group D-0.5 is 35.3+20. There is no statistically significant difference in demographic profile between two groups. It was also observed that there is no statistically significant difference in HR, SBP, DBP, MAP, RR and SpO2 in all point of time (p>0.05). According to sedation score in group D-0.3 72% patients were sleeping comfortably but easily arousable and 8% patients were in deep sleep, while in group D-0.5 70% were sleeping comfortably but easily arousable and 15% in deep sleep. Conclusion: After a loading dose of 1 μg/kg intravenously, an iv infusion of dexmedetomidine at a lower rate, i.e. 0.3μg/kg/hr is equally effective in providing sedation for patients undergoing surgeries under spinal anesthesia as 0.5μg/kg/hr.